From concept to approval: human genomic data integration with population observational data – insights from a Belgian pilot study - Nina Van Goethem; Johan Van der Heyden; Pierre Smith; Wannes Van Hoof; Harlinde De Schutter; Melissa Van Bossuyt; Karin De Ridder; Marc Van Den Bulcke; Emilie Cauët (Archives of Public Health)
Abstract Linking genomic data with population-level observational data sources offers a powerful approach to advance public health genomics research, providing a more comprehensive view of health outcomes by incorporating information on various health determinants. However, integrating data from scattered sources poses significant challenges. Genomic data, with its unique identifying properties and ethical concerns, is particularly sensitive and requires strict security measures and transparent participant communication to ensure confidentiality and maintain public trust. In Belgium, a pilot study has been set up to evaluate genetic and non-genetic health determinants associated with cancer. As a crucial step towards this scientific objective, the study also aims to assess the feasibility and complexity of linking genomics data with national population-based datasets. The process, ranging from conceptualisation and data discovery to securing approvals and finalising agreements, took two years. Each phase of this process offers opportunities to improve efficiency, enhance coordination between stakeholders, and address legal and ethical challenges. Establishing comprehensive, interoperable data catalogues can facilitate data discovery, while standardising data access requests can simplify processes. Pre-established partnerships or agreements can reduce administrative burdens and consequently, improve the timeliness of the research. Additionally, planning for sustainability in advance and rethinking consent procedures could reduce ad hoc approval procedures and support structural solutions for secondary use and linkage of health data in the public interest. This paper highlights practical challenges and considerations relevant to data linkage studies in general, offering insights for researchers conducting integrated public health genomics research.